A novel stainless steel needle electrode based on porous gold nanomaterials for the determination of copper in seawater. Issue 14 (27th March 2019) - Han, Haitao; Li, Ying; Pan, Dawei; Wang, Chenchen; Pan, Fei; Ding, Xiaoyan
Abstract : A stainless-steel needle electrode modified with porous gold and partially sacrificed polydopamine nanospheres was fabricated for the copper detection in seawater. Abstract : This study describes the fabrication of a porous gold (P-Au) nanomaterial-functionalized stainless steel acupuncture needle electrode (ANE) with the help of polydopamine (PDA) nanospheres, which were partially sacrificed for the voltammetric determination of copper in seawater. The PDA nanospheres were covered on sensing part, i.e., the needle tip, by the self-polymerization method and employed as a reductant and adhesion agent for the growth of gold nanomaterials with a porous structure and improved stability. The gold nanomaterials with a porous structure were self-assembled and deposited on the ANE with the reduction of AuCl4 − by PDA nanospheres, which were gradually sacrificed during this process. Moreover, there was no need to cover the protective layer additionally on the P-Au nanomaterial surface to prevent their peel off due to the strong adhesion capability of PDA. Owing to the excellent electrochemical properties of the P-Au nanomaterials and adhesion ability of the partially sacrificed PDA nanospheres, the modified ANE displayed remarkably improved performance and stability for the voltammetric determination of copper. Under optimal conditions, the linear range and detection limit of the modified ANE for copper ion determination are 0.7 nM to 1000 nM and 0.24 nM, respectively. Furthermore, the modified ANE has been successfully applied for the determination of copper in real seawater samples with satisfactory results.